The effectiveness of multilingual marketing/advertising messages by Nigerian manufacturers - Endong, Floribert Patrick Calvain (Journal of Print and Media Technology Research, 2023)
A well designed product’s package is very essential for effective communication as it facilitates the delivery and accurate decoding/interpretation of the marketing message(s) it contains. However, communication can become complicated when the marketing message is conceived to be bilingual or multilingual in view of targeting linguistically heterogeneous consumers. Because multilingual messages/texts’ designers usually make extensive use of typography and graphic design (to differentiate between linguistic codes involved in the composition of the message and to ultimately make these compositions readable and intelligible to potential decoders), we used a textual analysis and a user study to reveal incidences of reduced effectiveness – nay ineffectiveness – of marketing messages featuring on the packages of some products made in Nigeria or marketed by Nigerian firms. This study is based on a content analysis and two focus group discussions. The content analysis involved a dozen marketing messages by Nigerian manufacturers from the food and drugs sectors. It considered multilingual phrases and sentences contained in the messages as units of analysis. The paper presents a critique of these multilingual marketing messages with respect to the use of typography and graphics. It analyses the presence and use of typographical markers and graphics in advertising messages to differentiate between languages. It reveals that most Nigerian designers dominantly use punctuation and less spacing to differentiate between the linguistic codes employed in the construction of marketing/advertising messages. Furthermore, some of the multilingual phrases and sentences do not have typographical markers to emphasize these linguistic differences. The texts therefore remain mostly compact and hardly or less legible. The two focus group discussions conducted with multilingual and unilingual expatriates helped elicit consumers’ capacity to spot information presented in the multilingual message as well as explain how (in)effective the advertising messages may be in explaining the characteristics of the products been advertised. The discussants identified a number of weaknesses that pointed to the reduced effectiveness of the advertising messages.